Impact of Collaborative Learning Model on Improving Learning Outcomes and Thinking Skills of Junior High School Students - B S Kase, Emanuel (Universitas Tanjungpura, 2025)
This study aims to explore and analyze the impact of the collaborative learning model on improving learning outcomes and thinking skills of junior high school students. Utilizing a qualitative approach, data was collected through in-depth interviews, classroom observations, and document analysis involving students and teachers from several junior high schools implementing collaborative learning. The findings indicate that the collaborative learning model positively influences student learning outcomes, evidenced by enhanced comprehension of subject matter and improved academic performance. Furthermore, this model fosters critical thinking, problem-solving abilities, and effective communication among students. Participants reported increased engagement and motivation, as collaboration encourages peer interaction and shared responsibility for learning. Teachers noted that the collaborative approach facilitated a more inclusive classroom environment where diverse perspectives were valued. Challenges in implementation included managing group dynamics and assessing individual contributions; however, these were often mitigated through structured activities and clear guidelines. Overall, the study highlights the significance of collaborative learning in enhancing educational experiences for junior high school students. It provides valuable insights for educators seeking to adopt innovative teaching strategies that promote not only academic success but also essential skills needed for lifelong learning. Recommendations include ongoing professional development for teachers in collaborative methodologies and further research into long-term effects on student outcomes across various subjects.